CYBERSECURITY AND ARTIFICIAL INTELLIGENCE. A CRITICAL ANALYSIS (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The increasing complexity of cyber threats calls for the continuous evolution of cybersecurity strategies. This contribution explores the role of artificial intelligence (AI) in cyber- protection and defence, in particular, taking into account the revolution of cybersecurity practices brought about by advanced techniques such as machine learning and deep learning. The analysis of European and Italian strategies highlights the importance of an integrated approach involving technology, regulation and stakeholder cooperation. The risks related to the use of AI, including new vulnerabilities and potential ethical and social implications, are also discussed, with a view to analysing solutions for a more secure and resilient digital future.
Keywords: Cybersecurity; Resilience; Artificial intelligence; Risk; EU Law